A Review of Phytoestrogens and Their Association With Pelvic Floor Conditions. Issue 3 (May 2018) - Cardenas-Trowers, Olivia; Meyer, Isuzu; Markland, Alayne D.; Richter, Holly E.; Addis, Ilana
Abstract : Introduction: Urinary incontinence, pelvic organ prolapse, and fecal incontinence are pelvic floor disorders (PFDs) disproportionately experienced by postmenopausal women. Limited data exist suggesting that phytoestrogens may have an impact on the pathophysiology and symptom of PFDs. Purpose of Review: The aim of the study was to review the current literature addressing the role of phytoestrogens on PFDs, including the pathophysiology, symptom, treatment, and possible prevention. Findings: Qualifying literature spans from 2003 to 2017 and included 14 studies ranging from in vitro, animal, and observational studies to randomized clinical trials. Summary: Although the literature is limited, most studies on phytoestrogens and PFDs support associations with pathophysiologic mechanisms, symptoms, and treatment for urinary incontinence and pelvic organ prolapse, but not fecal incontinence. Less is known regarding the prevention of PFDs with phytoestrogen intake over time. Overall, the potential influence of phytoestrogens on PFDs is not well understood, and more research is needed. Abstract : Although the literature is limited, most studies on phytoestrogens and pelvic floor disorders support associations with pathophysiologic mechanisms, symptoms, and treatment for urinary incontinence and pelvic organ prolapse, but not fecal incontinence.